Neem secretory cells: developmental cytology and indications of cell autotoxicity - Canaveze, Yve [UNESP]; Scudeler, Elton Luiz [UNESP]; Rodrigues Machado, Silvia [UNESP] (Springer Nature, 2021)
The neem tree (Azadirachta indica A.Juss.) contains a range of biologically active compounds—mainly triterpenoids produced in single secretory cells, which are distributed among all plant parts. Neem secretions are toxic to animal cells, triggering autolytic mechanisms that culminate in cell disruption. However, little is known about the self-toxicity of these secretions to the cells that produce them. We carried out an anatomical, histochemical, and ultrastructural investigation of neem’s single secretory cells in the shoot apex and in young leaves. We evaluated the morphological changes as possible evidences of stress reactions to their own secretions. The subcellular apparatus involved in synthesis and compartmentation was consistent with hydrophilic and lipophilic secretions. Polymorphic plastids devoid of thylakoids and abundant smooth endoplasmic reticulum in the later stages of differentiation are comparable with previous reports on neem cotyledons with regard to terpenoid synthesis. However, secretions were compartmentalized within autophagic vacuoles and periplasmic spaces instead of in terpenoid vesicles. Cellular swelling, increased vesiculation, dilatation of endoplasmic reticulum cisternae, mitochondrial hypertrophy in the cristolysis process, autolytic vacuoles, and vacuolar degeneration culminating in protoplast autolysis are all consistent with early indications of autotoxicity. The signaling stress reaction mechanism was expressed as cytoplasmic deposits of calcium salt and by the expression of a 70-kDa heat-shock protein. The morphological and histochemical changes in the secreting cells are comparable with those described in animal cells exposed to neem oil. Our data provide evidence of cell damage and signaling reactions linked to these cells’ own secretions before autolysis.
Keywords: Azadirachta indica; Calcium deposits; Hsp70; Secretion; Ultrastructure